DAMPAK GLOBALISASI TERHADAP GAYA HIDUP PESERTA DIDIK DI SMA NEGERI 2 KOTA KUPANG - Ordi Un (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2020)
This research aims to know the impact of globalization on the lifestyle of students in SMA Negeri 2 Kupang. This research used a qualitative method which was intended deeply the lifestyle of students. The subjects of this study were students, teachers, and parents. As for data collection techniques used observation, interviews, and documentation. Data analysis techniques used data reduction, data display, and data verification. The results of the research show that SMA Negeri 2 Kupang city obtained the negative effects of globalization include how to dress students who no longer upload cultural values, uniforms that are supposed to be formally made like the clothes they see in the media. As for the positive realities of globalization such as students attire that is increasingly creative and broadly creative about lifestyles such as popular figures who inspire them. The lifestyle of SMA Negeri 2 Kupang city namely, they spend time in eating places and cafes, and their manner of dress often imitates famous artists and figures that inspire them.